Animacy is a Presupposition in Swahili - Pesetsky, Jonathan (My University, 2019)
In this paper, I argue that the phenomenon of animacy override in Swahili arises from the interaction between a syntactic structure with multiple nominal heads and general principles of distributed morphology. This syntactic analysis narrows the possibilities for a semantic analysis of animacy, strongly suggesting an approach previously proposed for gender in Romance languages. Specifically, I argue that Swahili has an interpretable +animate feature which denotes a partial function which is defined only on animate predicates of type et and which denotes the identity function where it is defined.
Keywords: Animacy; Swahili; NATURAL SCIENCES::Biology::Organism biology::Morphology